2021
DOI: 10.5194/acp-21-10527-2021
|View full text |Cite
|
Sign up to set email alerts
|

Isotopic signatures of major methane sources in the coal seam gas fields and adjacent agricultural districts, Queensland, Australia

Abstract: Abstract. In regions where there are multiple sources of methane (CH4) in close proximity, it can be difficult to apportion the CH4 measured in the atmosphere to the appropriate sources. In the Surat Basin, Queensland, Australia, coal seam gas (CSG) developments are surrounded by cattle feedlots, grazing cattle, piggeries, coal mines, urban centres and natural sources of CH4. The characterization of carbon (δ13C) and hydrogen (δD) stable isotopic composition of CH4 can help distinguish between specific emitter… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
33
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(40 citation statements)
references
References 98 publications
6
33
1
Order By: Relevance
“…Our sampling from East African cattle, to be detailed elsewhere [ 47 ], found δ 13 C CH 4 around −57‰, a range comparable to −57 to −52‰ values we previously found in Zimbabwean cattle [ 7 ] and broadly similar to Australian results of −59.7 ± 0.7‰ from grazing cattle, and −62 : 9 ± 1 : 3‰ from feedlot cattle [ 48 ]. However, we note our results are significantly more 13 C rich than the values around −65‰ found for sub-Saharan Africa by Chang et al .…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Our sampling from East African cattle, to be detailed elsewhere [ 47 ], found δ 13 C CH 4 around −57‰, a range comparable to −57 to −52‰ values we previously found in Zimbabwean cattle [ 7 ] and broadly similar to Australian results of −59.7 ± 0.7‰ from grazing cattle, and −62 : 9 ± 1 : 3‰ from feedlot cattle [ 48 ]. However, we note our results are significantly more 13 C rich than the values around −65‰ found for sub-Saharan Africa by Chang et al .…”
Section: Resultssupporting
confidence: 86%
“…However, like our results over Lake Wamala, Tyler et al [20] also found a range of values in other Kenyan wetlands, from −54‰ to −31‰, although with very high CO 2 measurements in many samples, suggesting complex perturbation. Our sampling from East African cattle, to be detailed elsewhere [47], found δ 13 C CH 4 around −57‰, a range comparable to −57 to −52‰ values we previously found in Zimbabwean cattle [7] and broadly similar to Australian results of −59.7 ± 0.7‰ from grazing cattle, and −62 : 9 ± 1 : 3‰ from feedlot cattle [48]. However, we note our results are significantly more 13 C rich than the values around −65‰ found for sub-Saharan Africa by Chang et al [49] (their fig.…”
Section: Wetlands Savannah and Farmlandssupporting
confidence: 87%
“…Therefore, accelerating the extraction and utilization of gas and transforming harmful gas into useable energy is a major trend in the energy field [ 11 ]. Lu et al and others said that in order to protect the living environment of mankind, the development and utilization of coalbed methane is regarded as an energy plan in the new century all over the world, which will inevitably promote the rapid development of China's coalbed methane mining industry [ 12 ]. Xie et al and others believe that the main problem at present is the low permeability of coal seam, and the adsorbed gas is difficult to be fully decomposed and absorbed, which brings great difficulties to the development of coalbed methane.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The Upper Silesian Coal Basin (USCB), where most mining activity occurs in Poland, is certainly a CH 4 emission hotspot in Europe. Atmospheric measurements at the USCB have mostly been performed in recent years (Swolkień, 2020;Luther et al, 2019;Gałkowski et al, 2020;Fiehn et al, 2020) and focused on the coal extraction activities. The CH 4 emission rates were estimated at the regional scale (Luther et al, 2019;Fiehn et al, 2020), with a relatively good agreement with the inventories (Luther et al, 2019;Fiehn et al, 2020;Gałkowski et al, 2020).…”
mentioning
confidence: 99%
“…Atmospheric measurements at the USCB have mostly been performed in recent years (Swolkień, 2020;Luther et al, 2019;Gałkowski et al, 2020;Fiehn et al, 2020) and focused on the coal extraction activities. The CH 4 emission rates were estimated at the regional scale (Luther et al, 2019;Fiehn et al, 2020), with a relatively good agreement with the inventories (Luther et al, 2019;Fiehn et al, 2020;Gałkowski et al, 2020). Swolkień (2020) performed direct measurements of CH 4 fluxes at individual shafts and emphasised the large variability of emission patterns between different sites.…”
mentioning
confidence: 99%